Preference discovery and experimentation - Kevin Cooke (Theoretical Economics, 2017)
I provide axiomatic foundations for a model of taste uncertainty with endogenous learning through consumption. In this setting, uncertainty is over an unobservable, subjective state space. Preference over lottery-menu pairs is sufficient to identify the state space and the learning process. In this model, the agent is viewed as if he learns the utility of an object upon its consumption. This information is used to improve choice from the follow-on menu. This implies a trade-off between consumption value and information leading to experimentation. I provide a behavioral definition of experimentation. While the literature focuses on identifying subjective states through a demand for flexibility, I show that experimentation also (partially) identifies taste uncertainty.
Keywords: D11; D83; 330; Taste uncertainty; learning through consumption; experimentation; endogenous learning; subjective state space; decision theory